2010
DOI: 10.1024/1661-4747/a000042
|View full text |Cite
|
Sign up to set email alerts
|

Lebensqualität von Kindern psychisch kranker Eltern

Abstract: Kinder psychisch kranker Eltern weisen im KINDL-R eine schlechtere Lebensqualität auf als eine Referenzstichprobe. Der Einfluss der Diagnosegruppe der elterlichen Erkrankung erweist sich als bedeutsam. Es gibt einige Zusammenhänge zu den unspezifischen elterlichen Erkrankungsvariablen: Je höher der Schweregrad der elterlichen Erkrankung, desto beeinträchtigter die familiäre Lebensqualität der Kinder. Wenn außerdem somatische Erkrankungen der Eltern vorliegen, ist die Lebensqualität stärker beeinträchtigt. Je l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
3
6
1
1
Order By: Relevance
“…The present study provides results based on assessments of the child him-or herself. Second, previous studies showed evidence for a negative effect of maternal acute depressive symptoms on child HRQoL (Wiegand-Grefe et al, 2010). We found similar results for mothers who were fully remitted from depression.…”
Section: Impact Of Maternal History Of Elm and Depression On Child Quality Of Lifesupporting
confidence: 84%
See 1 more Smart Citation
“…The present study provides results based on assessments of the child him-or herself. Second, previous studies showed evidence for a negative effect of maternal acute depressive symptoms on child HRQoL (Wiegand-Grefe et al, 2010). We found similar results for mothers who were fully remitted from depression.…”
Section: Impact Of Maternal History Of Elm and Depression On Child Quality Of Lifesupporting
confidence: 84%
“…So far, a negative association between general parental mental health problems and HRQoL of their children has been reported in previous research: Children of mentally ill parents show lower HRQoL than reference samples derived from the general population -whereas the quality of life is particularly affected in children with parents displaying a more depressive coping style (Giannakopoulos et al, 2009;Jeske et al, 2009;Wiegand-Grefe et al, 2012). Concordantly, parental depressive symptoms have been identified as significant predictor of lower child HRQoL (Wiegand-Grefe et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…the fifth finding), it has been shown that depression in parents of overweight children can lead to parenting stress [76] which, in turn, has been found to intensify the negative effect of being overweight on children's school well-being [77,78]. Further indirect evidence is that children whose parents are depressed are at a greater risk of being overweight [25,26,79] and of having poor school well-being [27,80] when compared to children whose parents are not depressed, and that overweight BMI is inversely associated with children's school well-being [24,68]. These relationships may exist because depressed parents with overweight children are more likely to engage in a parenting style that sets few household rules and responsibilities for children, and does not monitor children's healthy food choices, exercise or schooling [81,82].…”
Section: Discussionmentioning
confidence: 97%
“…Children of parents with a mental illness face childhoods that can be full of challenging experiences, threatening their quality of life, development and longterm outcomes [1][2][3][4]. However, these children are not an officially recognised group in the UK, and data and statistics are not gathered about them.…”
Section: Introductionmentioning
confidence: 99%